Communication and Cooperation Between the Medical Academy, Medical Association, and Local Government: Health Counseling Program After Recovery From Coronavirus Disease 2019 (COVID-19) in Daegu - Yun-A Kim; Geon Ho Lee; Keun-Mi Lee; Hae-Jin Ko; DongWook Lee; A-Sol Kim (Frontiers Media S.A., 2021)
We are currently experiencing the disaster of the COVID-19 pandemic. Since the first case of Coronavirus disease 2019 (COVID-19) was confirmed in South Korea on January 20, the number of COVID-19 cases in South Korea has been rapidly increasing until early March due to a local spread in Daegu, which is one of the eight metropolitan cities in South Korea with a population of 2.5 million. As the medical academy has social accountability as professionals, Daegu-Gyeongbuk branch of the Korean Academy of Family Medicine (Daegu-Gyeongbuk branch) developed the health counseling program for discharged COVID-19 patients. The Daegu-Gyeongbuk branch communicated with Daegu Medical Association and Daegu city for this program and incorporated available resources and capabilities as a leader of this program. This newly developed counseling program consists of medical consultations, sending healthcare brochures and medical supplies, and the appraisal at the end of the program. Not only COVID-19 related symptoms but also other psychological problems are also dealt with during consultations. This program started on March 18, and over 1,700 recovered patients have been receiving counseling as of April 28. Communication and cooperation between the medical academy, medical association, and government are essential to overcome the COVID-19 pandemic. Besides, we expect to apply this health counseling program and our model of setting this program cooperating with medical association and government to different infectious pandemic crisis.